Colour image encryption algorithm combining Arnold map, DNA sequence operation, and a Mandelbrot set - Jithin, K.C.; Sankar, Syam (Journal of information security and applications, 2020)
The third party misuse and manipulation of digital images is a threat to security and privacy of human subjects. The requirements to fulfil the security needs of digital images have led to the development of good encryption techniques. The proposed method of encryption scheme combines the techniques of chaotic image encryption and DNA (Deoxyribonucleic Acid) sequence operations. The encryption mechanism is applied separately on three channels (R, G and B) of the colour image with a suitable chaotic map. The map selection algorithm selects a good chaotic map based on image properties and other parameters. A method of DNA encoding is also applied after chaotic encryption. A new Mandelbrot Set based conditional shift algorithm is introduced to apply confusion effectively on R, G and B channels. Simulation and security analysis confirm that the proposed image encryption scheme demonstrates extraordinary performance in terms of security.